Interactions among tuberculosis, geographic environment and aerosols: evidence from the Kashgar region of China - Shang, Bo; Wei, Chengjing; Wang, Chenchen; Zheng, Yanling; Zhang, Liping (Frontiers in Public Health, 2025)
BackgroundAerosols can affect human health through mechanisms like inflammation, oxidative stress, immune dysregulation, and respiratory impairment. In high-pollution areas, airborne particles may promote the transmission of pathogens such as Mycobacterium tuberculosis. This study investigates the spatiotemporal distribution of tuberculosis, its association with air pollution, and potential sources in the geographically unique Kashgar region of Xinjiang, encircled by mountains and desert.MethodsKriging interpolation and time series observation were used to analyze spatiotemporal trends and identify hot and cold spots of tuberculosis (TB) incidence and air quality in Xinjiang from 2011 to 2023. Kruskal-Wallis and multiple comparisons were applied to assess regional differences. Meteorological clustering and trajectory analysis identified pollutant pathways and potential source areas, with hypotheses proposed for TB transmission routes.ResultsThe interaction between tuberculosis, the geographic environment, and aerosols in Xinjiang reveals a consistent spatial distribution of air quality index (AQI) and TB incidence, with overlapping hotspots and cold spots. The incidence rate of tuberculosis is “n/100,000.”Southern Xinjiang, shows higher TB incidence (235.31 ± 92.44) and poorer air quality (AQI: 64.19 ± 11.73) compared to Northern Xinjiang (TB: 83.82 ± 21.43, AQI: 53.90 ± 6.48). Significant regional differences in TB incidence (p < 0.0001) were confirmed, with post-hoc analyses indicating higher TB rates and worse air quality in Southern Xinjiang. Trajectory and concentration-weighted trajectory (WCWT) analysis identified dust from the Taklimakan Desert as a major contributor to PM2.5 and PM10 pollution, with values exceeding 150 μg/m3 for PM2.5 and 400 μg/m3 for PM10 in key areas like Aksu and Kashgar. The Kunlun and Tianshan mountain ranges serve as barriers that trap migrating dust, while meteorological patterns indicate that dust-laden trajectories extend further into the mountainous areas. This phenomenon exacerbates the spread of tuberculosis (TB) in the high-risk regions of southern Xinjiang.ConclusionThe study highlights a distinct interaction between TB, the geographic environment, and aerosols in southern Xinjiang. Poor air quality and elevated TB incidence overlap, particularly in Kashgar. Here, dust from the Taklimakan Desert, trapped by the Kunlun and Tianshan mountains, intensifies PM2.5 and PM10 pollution, further contributing to TB transmission in high-risk areas.